Medan Perjuangan Sosial Intelektual Hindu Bali Dalam Menghadapi Tantangan Islam Politik Kementerian Agama Republik Indonesia 1951-1958 - Santi Sihaloho, Melva; Wijaya, I Nyoman (Humanis; Vol 21 No 1 (2017), 2017)
Through the use of Social Struggle Field Boerdieu this study will not only talk about the position of Hindu Balinese intellectual groups. It includes discussing their tendency to reproduce, reshaping the Balinese social order in the face of the Islamic political group of the Ministry of Religious Affairs of the Republic of Indonesia (KAGRI). There are three research questions posed in this study, whose answers are sought by using the methodology of the political history, social history, and intellectual history of Kuntowijoyo’s. Besides, it is also used to assist the critical social science theory of poststructuralism, especially the generative structural theory of Boerdieu. The theory is used as the basis for thinking in digging and reconstructing the data and also placed within the framework of post-structuralism approach of Boerdieu style. In this way, the study was able to produce three conclusions from each of the research questions, which were then raised into a quintessence of conclusion that, in reproducing the social fabric of Balinese society in the face of the political Islamist group of the Ministry of Religious Affairs of the Republic of Indonesia (KAGRI) Balinese Hindu intellectuals put forward cultural thinking rather than economic thinking. Cultural thinking evolved from the habitus they had acquired since childhood. In facing the challenge of KAGRI political Islam group they are discouraging cultural thinking to the print media.